2018
DOI: 10.1002/bit.26572
|View full text |Cite
|
Sign up to set email alerts
|

Structural and metabolic responses of Staphylococcus aureus biofilms to hyperosmotic and antibiotic stress

Abstract: Biofilms alter their metabolism in response to environmental stress. This study explores the effect of a hyperosmotic agent–antibiotic treatment on the metabolism of Staphylococcus aureus biofilms through the use of nuclear magnetic resonance (NMR) techniques. To determine the metabolic activity of S. aureus, we quantified the concentrations of metabolites in spent medium using high-resolution NMR spectroscopy. Biofilm porosity, thickness, biovolume, and relative diffusion coefficient depth profiles were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A possible explanation for this observation is that antibiotic-damaged cells may continue to exhibit anabolic activity for some time, even as long as 24 h, although they are incapable of forming a visible colony on an agar plate. Other researchers have reported continued bacterial respiration following aggressive antimicrobial treatment (103)(104)(105)(106)(107)(108).…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation for this observation is that antibiotic-damaged cells may continue to exhibit anabolic activity for some time, even as long as 24 h, although they are incapable of forming a visible colony on an agar plate. Other researchers have reported continued bacterial respiration following aggressive antimicrobial treatment (103)(104)(105)(106)(107)(108).…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, the light may not have been able to penetrate the biofilms, hence no further antibiofilm effects were observed after PD activation. Secondly, lower oxygen levels within in vitro S. aureus biofilms, ( Kiamco et al., 2018 ) may reduce ROS generation. As ROS production is the mechanism by which PD action acts, ( Maisch et al., 2005 ) an anaerobic environment would limit such effects.…”
Section: Discussionmentioning
confidence: 99%
“…By studying it directly, unique snapshots of underlying physiological processes can be obtained. Metabolomics has grown in recent years as a powerful tool both for complementing other omics studies and for investigating the immense metabolic diversity found in prokaryotes (Stipetic et al, 2016;Kiamco et al, 2018).…”
Section: Discussionmentioning
confidence: 99%